THE EFFECT OF JOB STRESS AND WORKLOAD ON EMPLOYEE PERFORMANCE AT HOTEL MAHOGANY MUMBUL BALI - Luh Kadek Budi Martini (Jurnal Ekonomi & Bisnis JAGADITHA, 2018)
The objective of this study is to determine the effect of work stress and workload on employee performance. The study was conducted at Bali Mahogany Mumbul Hotel. The sample was all hotel employees amounting to 48 people. Data were collected by using observation method, interview with guidance of questionnaire; data were analyzed using multiple linear regression analysis. The result of the research showed that work stress and work load in silmultan have positive and significant influence on employee performance at Bali Mahogany Mumbul Hotel and partially that work stress have negative effect but not significant to employee performance, while work load has siginificant effect on the employee performance.